Reproductive Performance of Beef Cattle in Lowland and Highland Areas of Magelang District, Central Java - Syarifuddin, Ahmad (Journal of Applied Veterinary Science And Technology, 2025)
Background: Geographic location is one of the key factors influencing the reproductive performance of cattle. Environmental variables such as temperature, humidity, and rainfall directly affect the reproductive efficiency of cows. Purpose: This study aimed to compare the reproductive performance of beef cattle raised in highland and lowland areas. Method: A total of 60 productive female cows were surveyed, comprising 30 cows from the lowland area of Borobudur (230–240 m above sea level) and 30 from the highland area of Sawangan (450–1400 m above sea level). Data on calving interval and service per conception were obtained through field surveys of farmers maintaining artificial insemination records. The data were analyzed using a one-way ANOVA test. Results:  Reproductive performance was assessed based on calving interval and service per conception. Cows raised in the highland area of Sawangan demonstrated superior reproductive performance, with a calving interval of 429.66 ± 145.16 days and a service per conception rate of 1.5 ± 0.73, compared to 516.33 ± 168.72 days and 2.5 ± 1.61 in the lowland area of Borobudur. These findings suggest that higher altitudes with cooler and more stable climatic conditions contribute to improved reproductive efficiency. Conclusion: The results indicate that altitude has a significant influence on cattle reproductive performance. Cows raised in highland areas exhibited shorter calving intervals and lower service per conception rates compared to those in lowland areas. Cooler temperatures and lower humidity in highlands likely enhance reproductive outcomes. Farmers in lowland regions may improve reproductive efficiency by implementing cooling systems or adjusting breeding schedules. Further studies are recommended to identify additional environmental and management factors influencing cattle reproduction across different agroecological zones.